State export financial support of Brazilian manufactured products: A microeconometric analysis - Baggi Alvarez, R.; Kannebley Jr., S.; Mendonça, D. (EnANPAD 2018, 2018)
We investigate the impact of Brazilian state financing to exports - Proex, Exim and Drawback - on the performance of firms in foreign trade between 1998 and 2007. We focus on the risk of abandonment of export activity; number of destinations; and export value. We find a positive relationship between export programs and the intensive and extensive export margins, as well as with persistence in international trade. Supported firms had their chance to keep exporting augmented between 4% and 13%, increasing their number of destinations by up to 43% and the export value between 74% and 90%, although not all three programs are effective.